2017
DOI: 10.1111/pedi.12569
|View full text |Cite
|
Sign up to set email alerts
|

Association between interferon-induced helicase (IFIH1 ) rs1990760 polymorphism and seasonal variation in the onset of type 1 diabetes mellitus

Abstract: The IFIH1 rs1990760 polymorphism seems to be associated with the seasonal manifestation of T1DM. Our findings suggest that this virus receptor gene may contribute to T1DM manifestation primarily in the summer period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Genetic association between IFIH1 polymorphism and T1D development might be explained by the link of the disease with prior viral infection. Moreover, Jermedy et al found in their work that there is a seasonal manifestation of T1D was related to rs1990760 polymorphism as the AA genotype, that predisposes to the disease, was more frequent in patients who developed the disease in summer than in patients with onset in winter indicating that this virus receptor gene might influence T1D manifestation mainly during the summer months (59).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic association between IFIH1 polymorphism and T1D development might be explained by the link of the disease with prior viral infection. Moreover, Jermedy et al found in their work that there is a seasonal manifestation of T1D was related to rs1990760 polymorphism as the AA genotype, that predisposes to the disease, was more frequent in patients who developed the disease in summer than in patients with onset in winter indicating that this virus receptor gene might influence T1D manifestation mainly during the summer months (59).…”
Section: Discussionmentioning
confidence: 99%
“…CXCL10 [76], SIGLEC1 [77] and IL1R2 [78] have been suggested to be associated with neurological diseases. CXCL9 [79], SIGLEC1 [80], IL1R2 [81], KLF15 [82] and CD207 [83] [146], STAT4 [147], CXCL8 [148], KLF2 [149], ADM (adrenomedullin) [150], EGR1 [151], TRIB1 [152], SOD2 [153], OXSR1 [154], IL6R [155], CD44 [156], LRG1 [157], PFKFB2 [158], PACSIN2 [159], MYH9 [160], DOT1L [161], CXCL16 [162], PTEN (phosphatase and tensin homolog) [163], FOXO3 [164], DDIT4 [165], PINK1 [166], IQGAP1 [167], ADIPOR1 [168], MTMR3 [169], USF2 [170], SGK1 [171], GSTO2 [172], ETS2 [173], TKT (transketolase) [174], CMIP (c-Maf inducing protein) [175], THBD (granzyme A) [464], IFNG (interferon gamma) [465], IFIH1 [466], STAT1 [467], CCR5 [468], ADCY5 [469], MT2A [470], DPP4 [471], FASLG (Fas ligand)…”
Section: Discussionmentioning
confidence: 99%
“…In the present investigation, a total of 738 DEGs between COVID-19 samples and non COVID-19 samples were identified, consisting of 415 [76], SIGLEC1 [77] and IL1R2 [78] have been suggested to be associated with neurological diseases. CXCL9 [79], SIGLEC1 [80], IL1R2 [81], KLF15 [82] and CD207 [83] [146], STAT4 [147], CXCL8 [148], KLF2 [149], ADM (adrenomedullin) [150], EGR1 [151], TRIB1 [152], SOD2 [153] [162], PTEN (phosphatase and tensin homolog) [163], FOXO3 [164], DDIT4 [165], PINK1 [166], IQGAP1 [167], ADIPOR1 [168], MTMR3 [169] [464], IFNG (interferon gamma) [465], IFIH1 [466], STAT1 [467], CCR5 [468], ADCY5 [469], MT2A [470], DPP4 [471], FASLG (Fas ligand) [472], HLA-DMB [473], CD3D [474], CMKLR1 [475], ICOS (inducible T cell costimulator) [476] [492], CFB (complement factor B) [493], TLR7 [494], SLAMF1 [495], BPIFA1 [496], CD300E [497], TAP2 [498], CD48 [499], APOL1 [500], BACH2 [501], CD226 [502], CXCL12…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several studies showed that the IFIH1 A946T risk allele exerts its effect via the IFNβ-mediated response rather than through IFN-α, and IFN-β can promote persistent LCMV (lymphocytic choriomeningitis virus) infection, which causes enduring beta-cell damage (61)(62)(63)(64)(65). Intriguingly, a previous study indicated an association between the SNP rs1990760 and seasonal variation in the onset of T1DM and found that the predisposing gene was more likely to be associated with the onset of T1DM in summer (66). This finding may be explained by the theory that T1DM is caused by environmental factors in individuals with a genetically susceptible background.…”
Section: Ifih1mentioning
confidence: 99%